RESPONS GLUKOSA DARAH BENIH IKAN JELAWAT (Leptobarbus hoeveni Blkr) DALAM MEDIA YANG DIBERI EKSTRAK DAUN UBI JALAR (Ipomoea batatas) - Nur Rizki; Muhammad Sugihartono; Muarofah Ghofur (Universitas Batangahari Jambi, 2020)
Use of sweet potato leaf extract to determine the blood glucose response of jelawat fish (L. hoeveni, Blkr) seeds maintained in the media.This study aims to determine the optimal concentration of sweet potato leaf extract to reduce the stress level of Jelawat fish (L. hoeveni, Blkr) seeds by measuring blood glucose. In this study, four treatments were used with three replications using a concentration of 2ml / L sweet potato leaf extract, 4ml / L extract concentration, 6ml / L extract concentration, and control. The results showed that the 2ml / L extract concentration was the best because it was proven that the fish blood glucose response at every 1st, 6th, 12th hour, 24th hour, 168th hour fish (L. hoeveni, Blkr) seed blood glucose levels nettle nearly close to normal blood glucose levels in fish.